Experimental Study on Humidity Structure and p-value of Undisturbed Loess in High-risk Slope. Issue 3 (August 2020) - Jia, Yajun; Tang, Zhihong; Chen, Cunli; Liu, Naijun
Abstract: A long-term dry-wet cycle will cause changes in the internal structure of the loess, which will affect its permeability coefficient and slope properties. In this paper, through the dry-wet cycle test, the changes of permeability coefficient P value, porosity and dry density of undisturbed loess and remodelled loess under the action of dry-wet cycle are studied. Under the condition of dry-wet cycle, the permeability coefficient of undisturbed loess in high-risk slope decreases, and the permeability coefficient of remoulded loess increases. Remoulding the original loess of high-risk slopes due to soil erosion is more likely to cause gullies and internal erosion, accelerating the occurrence of original loess landslides and collapse of high-risk slopes.